E-business - Schneider, Gary P. (Course Technology Cengage Learning, 2013)
This title offers coverage of emerging online business strategies and technologies in the electronic commerce marketplace. It provides coverage of e-commerce growth in China and the developing world, social media and online marketing strategies, and more.